The changing epidemiology of the global paediatric HIV epidemic: keeping track of perinatally HIV‐infected adolescents. Issue 1 (18th June 2013) - Sohn, Annette H; Hazra, Rohan
Abstract : The global paediatric HIV epidemic is shifting into a new phase as children on antiretroviral therapy (ART) move into adolescence and adulthood, and face new challenges of living with HIV. UNAIDS reports that 3.4 million children aged below 15 years and 2 million adolescents aged between 10 and 19 years have HIV. Although the vast majority of children were perinatally infected, older children are combined with behaviourally infected adolescents and youth in global reporting, making it difficult to keep track of their outcomes. Perinatally HIV‐infected adolescents (PHIVA) are a highly unique patient sub‐population, having been infected before development of their immune systems, been subject to suboptimal ART options and formulations, and now face transition from complete dependence on adult caregivers to becoming their own caregivers. As we are unable to track long‐term complications and survival of PHIVA through national and global reporting systems, local and regional cohorts are the main sources for surveillance and research among PHIVA. This global review will utilize those data to highlight the epidemiology of PHIVA infection, treatment challenges and chronic disease risks. Unless mechanisms are created to count and separate out PHIVA outcomes, we will have few opportunities to characterize the negative consequences of life‐long HIV infection in order to find ways to prevent them.